If 2 ! ( n − 2 ) ! n ! and 4 ! ( n − 4 ) ! n ! are in the ratio 2 : 1 , then find n ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Since 4 ! ( n − 4 ) ! n ! is 2 1 of 2 ! ( n − 2 ) ! n ! , 2 ! ( n − 2 ) ! n ! = 2 4 ! ( n − 4 ) ! ( n ! ) . After we cross multiply and simplify the factorials, we now have ( 2 4 ) ( n ) ! ( n − 4 ) ! = 4 ( n ) ! ( n − 2 ) ! ) .
After dividing by n ! , we get ( 2 4 ) ( n − 4 ) ! = 4 ( n − 2 ) ! ) . From this, ( n − 4 ) ! ( n − 2 ) ! = 6 . This is the critical step - when we expand ( n − 2 ) ! , we have ( n − 2 ) ( n − 3 ) ( n − 4 ) ⋯ , which becomes ( n − 2 ) ( n − 3 ) ( n − 4 ) ! . Now, our previous expression becomes ( n − 2 ) ( n − 3 ) = 6 . Now we have a quadratic expression: ( n 2 − 5 n + 6 ) − 6 = 0 . We can simplify this into n ( n − 5 ) = 0 .
From this, either n = 0 , which is possible, but nonsensical since 0 : 0 can be in any ratio you want. The remaining solution is n − 5 = 0 , which makes n = 5 . We can verify this solution by checking the LHS, which is 2 ! 3 ! 5 ! = 2 5 ∗ 4 = 1 0 ; and the RHS, which is equal to 4 ! 5 ! = 5 . Therefore, the ratio of LHS:RHS is 1 0 : 5 , which is equal to 2 : 1 . This verifies the condition in the statement, and therefore our answer.
Problem Loading...
Note Loading...
Set Loading...
4 ! ( n − 4 ) ! n ! 2 ! ( n − 2 ) ! n ! 2 ! ( n − 2 ) ! 4 ! ( n − 4 ) ! ( n − 2 ) ( n − 3 ) 3 × 4 ( n − 2 ) ( n − 3 ) n 2 − 5 n + 6 n ( n − 5 ) ⟹ n = 1 2 = 2 = 2 = 6 = 6 = 0 = 5 n = 0 is unacceptable.